2014
DOI: 10.4172/1948-5948.1000158
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Carotenoid Production by Halorubrum Sp. TBZ126 Using Response Surface Methodology

Abstract: Carotenoids are one of the most diverse and broadly distributed classes of pigments in nature with a high number of biotechnological applications. Carotenoids have a broad range of functions, especially in relation to human health and their role as biological antioxidants. The increasing demand for consumption of natural carotenoids has raised interest in their bio-production. The objective of the present study was the analysis of environmental factors (temperature, pH and salinity) through response surface me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Similar results have been observed for Haloferax alexandrinus which exhibited high growth and carotenoid production under shaking conditions, reaching 2.06 mg total carotenoids g −1 DW . Halorubrum sp TBZ126 also showed higher concentrations of carotenoids upon optimized growth conditions, reaching 11.71 mg L −1 of total carotenoids …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar results have been observed for Haloferax alexandrinus which exhibited high growth and carotenoid production under shaking conditions, reaching 2.06 mg total carotenoids g −1 DW . Halorubrum sp TBZ126 also showed higher concentrations of carotenoids upon optimized growth conditions, reaching 11.71 mg L −1 of total carotenoids …”
Section: Resultsmentioning
confidence: 91%
“…Others strains of Halorubrum showed a similar range of growth temperature, for example Halorubrum alkaliphilum grows at an optimal temperature of 38°C but is able to grow between 20 and 44°C, Halorubrum luteum is able to grow between 33 and 37°C, Halorubrum sfaxense growth at optimal temperature of 37°C but is able to grow at 20–55°C and Halorubrum sp. TBZ126 is able to grow at 31–32°C . As shown in Figures g,h, light intensity has no significant effect on growth, but it influences on the total carotenoid content, which is about 25% higher in cells illuminated with light intensities of 200 µE m −2 s −1 than in cells grown in the dark, increasing from 20 to 25 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sikkander et al used a Box-Behnken design to determine the optimum factors affecting carotenoid production by Halorubrum sp. TBZ126, and the estimated coefficients and the corresponding p-values indicated that X1 (temperature), X2 (pH) and X3 (salinity) were significant factors for both cell growth and carotenoid production by this strain 15 . After extraction, the orange pigment in this study was characterized using FTIR, Raman spectroscopy, GC-MS, LC-MS and NMR methods.…”
Section: Discussionmentioning
confidence: 92%
“…Halophilic Archaea, from the families Halobacteriaceae and Haloferacaceae, have a red color that is mostly results from a special carotenoid they contain named "bacterioruberin". As recent investigations regarding the production of bacterioruberin show, the production of this rare carotenoid might be simply improved by enforcing modifications on light frequency, oxygen availability, pH, salinity, or temperature [41,223]. Furthermore, Haloarchaea are also organisms that produce several rare carotenoids such as salinixanthin [37,38].…”
Section: Other Carotenoidsmentioning
confidence: 99%